Raman Laser Spectrometer (RLS) calibration target design to allow onboard combined science between the RLS and MicrOmega instruments on the ExoMars rover. (23rd January 2020) - Lopez‐Reyes, Guillermo; Pilorget, Cedric; Moral, Andoni G.; Manrique, Jose Antonio; Sanz, Aurelio; Berrocal, Alicia; Veneranda, Marco; Rull, Fernando; Medina, Jesús; Hamm, Vincent; Bibring, Jean‐Pierre; Rodriguez, Jose Antonio; et al.
Abstract: The ExoMars rover, scheduled to be launched in 2020, will be equipped with a novel and diverse payload. It will also include a drill to collect subsurface samples (from 0‐ to 2‐m depth) and deliver them to the rover analytical laboratory, where it will be possible to perform combined science between instruments. For the first time, the exact same sample target areas will be investigated using complementary analytical methods—infrared spectrometry, Raman spectrometry, and laser desorption mass spectrometry—to establish mineralogical and organic chemistry composition. Fundamental for implementing this cooperative science strategy is the Raman Laser Spectrometer (RLS) calibration target (CT). The RLS CT features a polyethylene terephthalate disk used for RLS calibration and verification of the instrument during the mission. In addition, special patterns have been recorded on the RLS CT disk that the other instruments can detect and employ to determine their relative position. In this manner, the RLS CT ensures the spatial correlation between the three analytical laboratory instruments: MicrOmega, RLS, and MOMA. The RLS CT has been subjected to a series of tests to qualify it for space utilization and to characterize its behavior during the mission. The results from the joint work performed by the RLS and MicrOmega instrument teams confirm the feasibility of the "combined science" approach envisioned for ExoMars rover operations, whose science return is optimized when complementing the RLS and MicrOmega joint analysis with the autonomous RLS operation. Abstract : The ExoMars 2020 mission rover provides the unique opportunity of performing in situ analysis of Martian subsurface samples at the mineral grain scale. Furthermore, this will be done at the same spot with the analytical instruments of the rover. The RLS calibration target plays a key role in the spatial correlation between the RLS and MicrOmega instruments. Also, the synergy and improved results obtained from the combined analysis of RLS and MicrOmega are presented in the document.